Implementing Education for All—Whose agenda, whose change? The case study of the Ghana National Education Campaign Coalition - Strutt, Courtney; Kepe, Thembela (International journal of educational development, 2010)
With the onset of the Education for All (EFA) agenda in 1990, the international development community has seen new forms of international cooperation forming around the pledge for EFA. This paper analyzes a case study of activities and challenges of a civil society coalition, the Ghana National Education Campaign Coalition (GNECC), in pursuing the goals of Education for All within the national context of Ghana. The key findings of this case study concern the major challenges that GNECC faces as a national education coalition implementing the global agenda of EFA. These challenges include broad goals and objectives, unsustainable funding, and a lack of local participation and ownership of activities. The research concludes that while GNECC has been successful in implementing certain aspects of national and international programming, at the local level it remains woefully behind as a result of inadequate funding of community level activities, poor participation, and external impetus. In essence, GNECC has been operating as a national activity implementing NGO as opposed to a collaborative community coalition aimed at resolving educational issues, leading to the conclusion that an externally initiated coalition is not the most influential tool for achieving progress on international agendas such as EFA.